D–A–A‐Type Organic Dyes for NiO‐Based Dye‐Sensitized Solar Cells. Issue 31 (30th September 2015) - Wu, Fei; Liu, Jianlin; Li, Xi; Song, Qunliang; Wang, Min; Zhong, Cheng; Zhu, Linna
Abstract: Three new D–A–A‐type organic sensitizers – W1, W2, and W3 – have been synthesized and applied for p‐type dye‐sensitized solar cells. For the first time, the electron‐withdrawing 2, 1, 3‐benzothiadiazole (BT) unit has been applied as the π‐bridge between the triphenylamine donor and different acceptors in these dye molecules. It turns out that these dyes all exhibit power conversion efficiencies exceeding 0.1 %, and that the best performance is achieved by the dye W2, with an octyl 2‐cyanoacrylate acceptor. It shows a power conversion efficiency of 0.166 %, with a short circuit current of 4.16 mA cm –2 and an open circuit voltage of 0.121 V. The higher light‐harvesting efficiency leads to a higher photocurrent in W2. In addition, electrochemical impedance spectroscopy (EIS) studies suggest slower charge recombination at the metal oxide/electrolyte interface and a faster hole‐transporting ability of W2. The factors together may account for the higher power conversion efficiency of W2. This work demonstrates rational design of these dye molecules for the construction of efficient p‐type sensitizers. Abstract : Three new D–A–A‐type organic dyes for p‐type dye‐sensitized solar cells were synthesized. The electron‐withdrawing 2, 1, 3‐benzothiadiazole (BT) unit was used for the first time in such dyes as the π‐bridge between the triphenylamine donor and different acceptors. W2 shows a power conversion efficiency of 0.166 %, with a short circuit current of 4.16 mA cm –2 and an open circuit voltage of 0.121 V.